The Public Communication Campaign Strategy of The Ministry of Communication and Digital in Combating Online Gambling in Indonesia - Listya Widyasari, Karina; Ardiyanto , Indra (Journal Research of Social Science, Economics, and Management, 2026)
Online gambling is a growing social problem in the digital era, negatively impacting society. The Ministry of Communication and Digital (Kemkomdigi) plays a significant role in addressing this issue through public communication campaigns. This study aims to analyze the campaign strategies implemented by Kemkomdigi, the planning processes involved, and the challenges faced. A qualitative research method was employed, with in-depth interviews conducted with informants from Kemkomdigi, the public, and communication experts. The findings indicate that collaboration with various stakeholders and the implementation of appropriate campaign strategies are key to combating online gambling. The study reveals that while multi-channel communication approaches have proven effective in raising public awareness, challenges related to disinformation, limited digital literacy in rural areas, and budget constraints continue to hinder the overall effectiveness of the campaigns. These findings have significant implications for developing more targeted, data-driven, and adaptive public communication strategies to address social issues in the digital era. It is recommended that Kemkomdigi continue to strengthen digital literacy and engage the community in eradicating online gambling through more operational and measurable program designs.